Elephants in the farm – changing temporal and seasonal patterns of human-elephant interactions in a forest-agriculture matrix in the Western Ghats, India - Anoop, N. R.; Krishnan, Siddhartha; Ganesh, T. (Frontiers in Conservation Science, 2023)
Accelerating levels of human-elephant conflicts (HEC) have become a topic of major concern in conservation efforts of endangered Asian elephants (Elephas maximus) throughout their range. Wayanad plateau (WP) is a key summer habitat of Asian elephants in the Brahmagri-Nilgiri Eastern Ghats elephant landscape (Nilgiris), harbouring the largest breeding population in Asia. With the increase in human population density and consequent forest loss, HEC amplified in frequency and intensity in Wayanad. We assessed the drivers of HEC in a temporal and spatial context by integrating questionnaire surveys, compensation claims for crop loss, and individual identification of crop-raiding elephants. The ordinal regression analysis showed that season and proximity to the forest boundary were the major drivers of conflict. The pattern of conflict is spatially heterogeneous, and there is peak crop depredation during the jackfruit and mango season (May - September), followed by paddy season (September-December). The conflict has resulted in the removal of jackfruit and mango trees from farmlands and stopped cultivation of several crops that attract elephants. This has impacted rural food supply, economic well-being, local biodiversity, and human-elephant coexistence. We discuss effective and locally appropriate conflict mitigation and management strategies which can apply in human-dominated landscapes.